Activating the objective of preserving wealth in lease contracts that end with ownership - Mezouzia, Abderrahmane; Belkacemi, Salima (The International tax journal, 2025)
This research study aims to examine the objective of preserving wealth as one of the fundamental principles of Islamic law by integrating theoretical foundations with practical applications. The first section defines this objective, its position among the goals of Islamic law and its relevance to necessities. It also explores how Islamic law cares for wealth and its resources and the most important legal means of ensuring and preserving wealth. The second section focuses on the practical application of this objective through the model of leasing ending in ownership, revealing how it can be activated within this framework.